2003
DOI: 10.1074/jbc.m307067200
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing of the Human Cyclin D-binding Myb-like Protein (hDMP1) Yields a Truncated Protein Isoform That Alters Macrophage Differentiation Patterns

Abstract: We have cloned two novel, alternatively spliced messages of human cyclin D-binding Myb-like protein (hDMP1). The known, full-length protein has been named hDMP1␣ and the new isoforms, hDMP1␤ and hDMP1␥. The hDMP1␣, -␤, and -␥ splice variants have unique expression patterns in normal hematopoietic cells; hDMP1␤ mRNA transcripts are strongly expressed in quiescent CD34؉ cells and freshly isolated peripheral blood leukocytes, as compared with hDMP1␣. In contrast, activated T-cells and developing myeloid cells, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
123
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 76 publications
(126 citation statements)
references
References 46 publications
3
123
0
Order By: Relevance
“…One copy of the genes at the hDMP1 locus was reportedly deleted in all the tumor cells with chromosome 7q abnormalities regardless of the detailed karyotype, suggesting that one allele loss of hDMP1 could contribute to 7q-malignancies that are refractory to conventional chemotherapy . It has been reported that the hDMP1 locus encodes at least three splicing variants, that is hDMP1a, b and g (Tschan et al, 2003). The full-length hDMP1a corresponds to murine Dmp1, which positively regulates the p19 Arf -p53 pathway (Tschan et al, 2003).…”
Section: The Human Dmp1 Gene and Cancermentioning
confidence: 99%
“…One copy of the genes at the hDMP1 locus was reportedly deleted in all the tumor cells with chromosome 7q abnormalities regardless of the detailed karyotype, suggesting that one allele loss of hDMP1 could contribute to 7q-malignancies that are refractory to conventional chemotherapy . It has been reported that the hDMP1 locus encodes at least three splicing variants, that is hDMP1a, b and g (Tschan et al, 2003). The full-length hDMP1a corresponds to murine Dmp1, which positively regulates the p19 Arf -p53 pathway (Tschan et al, 2003).…”
Section: The Human Dmp1 Gene and Cancermentioning
confidence: 99%
“…The nontargeting vector SHC002 was used as a control. Lentivirus production and transduction of cells was done as described earlier (14). The vectors contain a puromycin resistance gene and stably transduced cell populations were selected for 2 weeks using puromycin at the concentration 1.5 mg/mL.…”
Section: Translational Relevancementioning
confidence: 99%
“…Lentivirus and retrovirus preparation and transduction Lentiviral vectors expressing hsa-miR-29b precursor or a scrambled vector, anti-sense miR-29b (pMIRRZIP-29b-PA-1) or a control scrambled hairpin vector (System Biosciences, Mountain View, CA, USA) as well as c-Myc were prepared and used to transduce lung cancer cells as described (Tschan et al, 2003). ID1 overexpression was performed using retroviral vectors as described (Gautschi et al, 2008).…”
mentioning
confidence: 99%